2015
DOI: 10.1177/0959683615591356
|View full text |Cite
|
Sign up to set email alerts
|

Holocene records of environmental change in High Plains playa wetlands, Kansas, US

Abstract: Holocene environmental change is poorly characterized throughout much of the High Plains. Playa wetlands are sites with appreciable potential for reconstructing environmental change because of their environmental sensitivity. Radiocarbon, litho- and magneto-stratigraphic, and stable carbon isotope (δ13C) data for four playas on the Kansas High Plains indicate significant change occurred throughout the Holocene, which had profound impacts on playa ecosystem functions (e.g. groundwater recharge, surface water st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Therefore, having knowledge about the different types of playa surfaces and their physicochemical characteristics helps to identify dust-prone surfaces and could be a step forward in their control. In this regard, several studies have analysed playa geomorphic surfaces and their potential in dust generation (Reynolds et al, 2007;Quick et al, 2009;Halleaux and Rennó, 2014;Bowen and Johnson, 2015;Wurtsbaugh et al, 2017). For example, Wurtsbaugh et al (2017) have shown that the release of particles from the dried bed of Owens Lake in California increased the PM 10 levels and caused respiratory problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, having knowledge about the different types of playa surfaces and their physicochemical characteristics helps to identify dust-prone surfaces and could be a step forward in their control. In this regard, several studies have analysed playa geomorphic surfaces and their potential in dust generation (Reynolds et al, 2007;Quick et al, 2009;Halleaux and Rennó, 2014;Bowen and Johnson, 2015;Wurtsbaugh et al, 2017). For example, Wurtsbaugh et al (2017) have shown that the release of particles from the dried bed of Owens Lake in California increased the PM 10 levels and caused respiratory problems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wurtsbaugh et al (2017) have shown that the release of particles from the dried bed of Owens Lake in California increased the PM 10 levels and caused respiratory problems. Bowen and Johnson (2015) found that the increase in soil humidity decreases the likelihood of dust generation on a playa surface. Reynolds et al (2007Reynolds et al ( , 2009 found that dry playas of Mojave desert were prone to dust generation following wet periods.…”
Section: Introductionmentioning
confidence: 99%
“…About 100-300 million tons of dust are emitted into the atmosphere each year (Varga et al, 2014). These landform units are commonly found in the western United States (Bowen and Johnson, 2015;Collins et al, 2018), North Africa (Prospero et al, 2002;Mahowald et al, 2006), Central Asia (Ziyaee et al, 2018), and northern China (Tao et al, 2020;Hao and Li, 2021). There are hundreds of lakes with areas of greater than 50 km 2 in northern China, and under the drastic climate change and unreasonable human development, a large number of these lakes have shrunk and become dry lake beds.…”
Section: Introductionmentioning
confidence: 99%
“…Playas are ephemeral or desiccated lakes found throughout arid and semi‐arid regions of the world (Goudie and Wells, ; Yechieli and Wood, ; Shaw and Bryant, ; Goudie, ). In North America, they have been described in the Northern (Last and Schweyen, ), Central (Bowen and Johnson, , ; Bowen et al ., ) and Southern Great Plains (Wood et al ., ; Gustavson et al, ; Holliday, ; Holliday et al ., ), arid basins of the southern Pacific Coast Ranges (Eghbal et al ., ), the Mexican Plateau (Alcocer and Escobar, ) and throughout the Basin and Range region (Currey, ; Scuderi et al ., ). Due to their ephemeral nature playas are highly sensitive to climatic fluctuations and are influenced, often simultaneously, by fluvial, lacustrine and eolian processes (Holliday, ; Holliday et al ., ; Bowen and Johnson, , ; Rich, ), making them useful paleoenvironmental archives.…”
Section: Introductionmentioning
confidence: 99%